Dialogue and dialogicality in searches for personality-oriented senses of education and culture - Troitska, O. M.; Троїцька, О. М.; Троицкая, О. М.; Lytvyna, Yu. S.; Литвина, Ю. С. (My University, 2017)
In the article the problem of dialogue an dialogicality introduction into the learning process is considered. There has been marked the dialogicality is a natural man’s quality and it is considered as a capacity to comprehend the world mysteries and rebuild the world on the basis of objectively established laws and moral-ethic principles, norms and regulators of people’s life activity. Besides, dialogicality involves the acquirement the general civilization rules of interaction between representatives of various cultures, subcultures and countercultures. It has been proved that in this context education possesses the significant possibilities, which is getting more and more polycultural nowadays, i.e. it ensures culture-appropriate (continuous, integrative, contextual, consensual-pluralistic) system of personality socialization with particular groundwork in culture-education programs, cross-cultural literacy, personality development etc. The authors focus attention on contradictions of spiritual development of a personality in the process of dialogical interaction solution of which explicates the value-sense form of existence of a human in the world.

У статті порушується проблема діалогу та введення діалогічності у сучасну систему освіти та культури. Відзначено, що діалог є природною якістю людини та розглядається як здатність у плюралізмі думок пізнавати таємниці світу та перебудовувати його. Крім цього, діалогічність передбачає засвоєння загальноцивілізаційних правил взаємодії презентантів різних культур, субкультур та контркультур. Відстоюється думка про те, що значні можливості у цьому плані має освіта, яка у сучасному світі стає більш полікультурною, тобто такою, що забезпечує культуровідповідну (неперервну, інтегративну, контекстуальну, консенсуально-плюралістичну) систему соціалізації особистості з певними наробками з культурно-освітніми програмами, крос-культурної грамотності, особистісного розвитку. Автори акцентують увагу на суперечності духовного розвитку особистості в процесі діалогічної взаємодії, розв’язання яких експлікує ціннісно-смислову форму буття людини в світі.

В статье поднимается проблема диалога и введения диалогичности в современную систему образования и культуру. Отмечено, что диалогичность является природным качеством человека и рассматривается как его способность в плюрализме мыслей постигать тайны мира и перестраивать мир. Кроме того, диалогичность предусматривает усвоение общецивилизационных правил взаимодействия презентантов самых разных культур, субкультур и контркультур. Отстаивается мысль о том, что значительными возможностями в этом плане обладает образование, которое в современном мире становится всё более поликультурным, т.е. обеспечивающим, по нашему мнению, культуросообразную (непрерывную, интегративную, контекстуальную, консенсуально-плюралистическую), систему социализации личности с определенными наработками по культурно-образовательным программам, кросс-культурной грамотности, личностного развития. Авторы акцентируют внимание на противоречии духовного развития личности в процессе диалогического взаимодействия, решение которых эксплицирует ценностно-смысловую форму бытия человека в мире.
Troitska O. M. Dialogue and dialogicality in searches for personality-oriented senses of education and culture / O. M. Troitska, Yu. S. Lytvyna // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 18. - С. 139-142.
Keywords: dialogue; dialogicality; cultural-educational space; praxeology; universals; діалог; діалогічність; культурно-освітній простір; праксеологія; універсалії; диалог; диалогичность; культурно-образовательное пространство; праксеология; универсалии